Developing communities - Kenny, Susan; Hand, Tammy (Cengage Learning Australia, 2022)
Community development is a living field of theory and practice. The enduring features of community development include the commitment to human rights; the empowerment of ordinary people, and especially those who are disadvantaged and oppressed: and support for communities to exert greater control over decisions that affect their lives.